Peningkatan Hasil Belajar Siswa Menggunakan Model Problem Based Learning Pada Mata Pelajaran PAI Kelas IV UPTD SD Negeri 03 Andiang - Yeni Susila; Syawaluddin Syawaluddin; Deslita Deslita; Delfiyanti Delfiyanti; Hidayati Sadli; Dila Yanti Safitri (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) class IV at UPTD SD Negeri 03 Andiang through the application of the Problem Based Learning (PBL) learning model. The background of this study is based on the low learning outcomes of students identified from daily grades which show that many students have not reached the Criteria for Completeness of Learning Objectives (KKTP). The PBL model was chosen because it is believed to be able to train students to think critically and solve problems independently, which is in accordance with the characteristics of 21st century learning. This research is a Classroom Action Research (PTK) conducted in four cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation sheets, and interviews. Student learning Through the results of this research, it shows that the method of giving learning tasks and resitation has a positive impact on improving student learning achievement. This can be seen from the students' understanding of the material presented by the teacher (learning completeness increased from Pre-cycle, cycle I, II, III) and IV, namely 33%, 58%, and 81% respectively. In cycle IV, classical student learning completeness was achieved 100%. Based on these findings, it can be concluded that the application of the Problem Based Learning model is effective in improving student learning outcomes in Islamic Religious Education class IV at UPTD SD Negeri 03 Andiang. Therefore, this learning model can be used as an alternative learning method that is more interesting and effective in the classroom.